Exploring facilitators and barriers to patient-provider communication regarding diabetes self-management - Brenna O. Kirk; Raihan Khan; Danielle Davidov; Usha Sambamoorthi; Ranjita Misra (Elsevier, 2023)
Objective: Long-term type 2 diabetes management requires open communication between a patient and their provider for self-care adherence. This study explored facilitators and barriers to diabetes-specific communication in West Virginia, a medically underserved state with the highest prevalence of diabetes (16.2%) in the U.S. Methods: A secondary qualitative analysis was conducted using data from semi-structured interviews (n = 34) and 4 focus groups (n = 23) with participants of a diabetes education program. Transcripts were analyzed using thematic analysis. Results: Three facilitators to patient-provider communication emerged: "Patient-Provider Partnership", "Provider Accessibility", and "Empowerment Through Education". Partnership with providers, especially those who were accessible outside of scheduled appointments, and empowerment obtained through diabetes education facilitated diabetes-specific patient-provider communication. However, barriers included "Providers' Focus on 'Numbers' Rather than Patient Concerns", "Patient Lack of Preparation for Appointments", and "Providers 'Talking Down to' Patients". Conclusion: The findings highlight patient- and provider-related factors that impact diabetes-specific communication. Innovation: Previous interventions have trained providers in communication skills. Despite some success, challenges in implementation remain considering providers' limited time and overwhelming demands. This study suggests that diabetes education programs incorporating communication and self-advocacy skills could be a promising alternative as they can empower patients to communicate their diabetes-specific needs/preferences with providers.